The Cooking and Pneumonia Study (CAPS) in Malawi: A Nested Pilot of Photovoice Participatory Research Methodology. - Jane Ardrey; Nicola Desmond; Rachel Tolhurst; Kevin Mortimer (PLoS ONE, 2016)
The Cooking and Pneumonia Study (CAPS) is a village-level randomised controlled trial of an advanced cookstove intervention to prevent pneumonia in children under the age of 5 in rural Malawi (www.capstudy.org). The trial offers a unique opportunity to gain understanding about the social and cultural factors that may facilitate sustained use of improved cookstoves. In January 2015, the use of Photovoice as a participatory research methodology was piloted at the CAPS Chikhwawa site. Photovoice is a photographic technique that allows communities (including women and marginalised groups) to share knowledge about their perspectives and priorities. Four households were given digital cameras and asked to collect images over 24-48 hours and were then interviewed on film about their selection. This resulted in over 400 images and a one hour long film that revealed community concerns and could be thematically analysed. The collection of interview data through film was useful for capturing discussion and was acceptable to participants. Photovoice is a feasible participatory research methodology that can play a valuable role in qualitative studies of improved cookstove adoption in challenging resource poor settings.